2015
DOI: 10.5114/kitp.2015.50565
|View full text |Cite
|
Sign up to set email alerts
|

ANAESTHESIOLOGY AND INTENSIVE CARE Prognostic value of sCD14-ST (presepsin) in cardiac surgery

Abstract: IntroductionPrediction of complications and mortality after cardiac surgery is an important aspect of timely correction of these conditions. One possibility in this case is the use of biomarkers and some prognostic scores.Aim of the studyTo study the prognostic value of presepsin (PSP) as a predictor of postoperative complications development in cardiosurgical patients.Material and methodsPatients operated for acquired heart diseases with cardiopulmonary bypass (CPB) were included in the study (n = 51, age: 58… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 10 publications
3
21
0
1
Order By: Relevance
“…In our study levels of presepsin were significantly higher in patients who developed VAP compared to those with SIRS and significantly higher in patients with sepsis compared to those with VAP or SIRS. These results are in line with few studies that measured levels of sCD14-ST in blood samples for local infection diagnosis [21][22][23] . In study of Shozushima et al 22 presepsin levels were significantly higher in patients with local infection, sepsis, and severe sepsis than in patients without infection.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study levels of presepsin were significantly higher in patients who developed VAP compared to those with SIRS and significantly higher in patients with sepsis compared to those with VAP or SIRS. These results are in line with few studies that measured levels of sCD14-ST in blood samples for local infection diagnosis [21][22][23] . In study of Shozushima et al 22 presepsin levels were significantly higher in patients with local infection, sepsis, and severe sepsis than in patients without infection.…”
Section: Discussionsupporting
confidence: 90%
“…In study of Shozushima et al 22 presepsin levels were significantly higher in patients with local infection, sepsis, and severe sepsis than in patients without infection. Similarly, Popov et al 23 showed significantly higher values of presepsin in the group of patient with infectious complications than in those without infections following cardiac surgery. In our study, however, we measured biomarkers levels only after the clinical diagnosis of infection was made.…”
Section: Discussionmentioning
confidence: 80%
“…Reiner et al [3] demonstrated a strong association between the precursor of presepsin and the incidence of cardiovascular disease in the elderly. Additionally, Popov et al [23] recently analyzed the prognostic value of presepsin as a predictor of postoperative complications in patients having surgery for acquired heart disease. In particular, heart failure was strongly associated with increased levels of the biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Popov et al evaluated the prognostic value of PSP in patients operated for acquired heart diseases and revealed that PSP levels were increased in patients with acute HF and acute coronary syndrome without infection. (22) In our study, median PSP level was 684 pg / mL ranging from 147 to 5529 pg / mL in the patient group. Liu et al declared median PSP levels as 787 pg / mL for severe sepsis and 1084 pg / mL for septic shock in an emergency department.…”
Section: Discussionmentioning
confidence: 47%